2022
DOI: 10.1155/2022/3691638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forest Management on Carbon Stock of Tropical Moist Afromontane Forest

Abstract: Moist tropical forests have a significant role in provisioning and regulating ecosystem services. However, these forests are under threat of deforestation and forest degradation. In Ethiopia, the moist evergreen Afromontane forests have the potential for carbon storage and support a high diversity of plant species. However, it is under severe threat of deforestation and degradation.This investigation was conducted to obtain adequate information on the carbon stock potential of the moist Afromontane forest of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…However, compared to other studies, the species richness of 79 was relatively higher despite the smaller sample plot size used in this study (0.071 ha). For instance, Masresha and Melkamu (2022) in Ethiopia reported 12 different values of species richness ranging from 36-78 tree species, Boz and Maryo (2020) from Ethiopia reported a total of 76 woody species representing 40 families in a dry semi-evergreen Afromontane forest from 64 (0.04 ha) sample plots, Daba et al (2022) from the moist Afromontane forest of southwestern Ethiopia recorded a total of 68 tree and shrub species and 33 families from 100 plots of 20m × 20m and Feroz et al (2016) reported 40 species (in 0.16 ha) in tropical wet evergreen forest in Bangladesh.…”
Section: Species Compositionmentioning
confidence: 99%
“…However, compared to other studies, the species richness of 79 was relatively higher despite the smaller sample plot size used in this study (0.071 ha). For instance, Masresha and Melkamu (2022) in Ethiopia reported 12 different values of species richness ranging from 36-78 tree species, Boz and Maryo (2020) from Ethiopia reported a total of 76 woody species representing 40 families in a dry semi-evergreen Afromontane forest from 64 (0.04 ha) sample plots, Daba et al (2022) from the moist Afromontane forest of southwestern Ethiopia recorded a total of 68 tree and shrub species and 33 families from 100 plots of 20m × 20m and Feroz et al (2016) reported 40 species (in 0.16 ha) in tropical wet evergreen forest in Bangladesh.…”
Section: Species Compositionmentioning
confidence: 99%
“…In the study area, carbon stock increased by 41.4% from open, unmanaged forest to forest under area exclosures. There are numerous arguments that forest management interventions improve the carbon stock potential of forest ecosystems (Bazezew et al., 2015a , 2015b ; Daba et al., 2022 ; Jati, 2012 ; Noormets et al., 2014 ). Furthermore, forest under area exclosures improves carbon stock potentials when compared to open forest patches, and it has intermediate biomass and carbon stock potential when compared to open forests and reference church forests (Kassaye et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forests contain most of the terrestrial biodiversity and are estimated to store about 289 Gt of biomass carbon (Apguaua et al 2015;FAO 2022). The terrestrial vegetation alone is estimated to store approximately 450-650 Gt of carbon (Daba et al 2022). Forests also support life of many living organisms on earth and are a source of livelihood for more than 1.4 billion people worldwide (Kendie et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to Karki et al (2017), deforestation prevention has been generally accepted as a promising mitigation strategy for mitigating climate change through carbon negotiation mechanisms like REDD+ (reduced emission from deforestation and forest degradation, plus forest conservation, sustainable forest management, and enhancement). REDD+ was devised under the United Nations Framework Convention on Climate Change (UNFCCC) to combat CO2 emissions (Houghton 2012;Daba et al 2022). However, for a participating country to benefit from the carbon credit market, a precise and verifiable estimate of carbon stock data from the major carbon pools is necessary (Corbera and Schroeder 2011;Daba et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation